The Successful Treatment of Multi-Resistant Colonized Burns with Large-Area Atmospheric Cold Plasma Therapy and Dermis Substitute Matrix-A Case Report - Moritz R. Milewski; Frederik Schlottmann; Vincent März; Thorben Dieck; Peter M. Vogt (MDPI AG, 2024)
The treatment of severe burn injuries, which occur particularly in the context of armed conflicts, is based on a multimodal treatment concept. In addition to complex intensive care therapy, the surgical reconstruction options of plastic surgery and typical antiseptic wound treatment are the main focuses. In recent years, atmospheric cold plasma therapy (ACPT) has also become established for topical, antiseptic wound treatment and for the optimization of re-epithelialization. This case report shows a successful treatment of extensive burn injuries using dermal skin substitute matrix and topical treatment with a large-area cold plasma device to control multi-resistant pathogen colonization. This case report illustrates the importance of ACPT in burn surgery. However, larger case series and randomized controlled trials in specialized centers are needed to assess its place in future clinical practice.